Two alternative chormatography methods assited by the sulfonic acid moiety for the determination of furosine in milk - Artavia González, Graciela (2018)
N6-(2-(2-Furanyl-2-oxoethyl))-l-lysine (furosine) is a deteriorative reaction product that is produced during heat treatment and storage of milk. This compound affects the quality of commercial dairy products. Accurate determination of furosine is necessary as it may serve as a measure of the degree of protein degradation in dairy products. In this article, two HPLC based methods (1. a novel ion-pairing reagent 2. a strong cation exchange column) are proposed to quantify furosine. These methods were optimized and validated for their application to analyze fluid milk and dried milk powder. •Two methods that can be used for routine milk quality control, including heat damage and adulteration, were developed. •Compared to previous methods, the modified procedures herein using aromatic sulfonic acids (a pairing agent or covalently bound to a matrix on a strong cation exchange column) provide less expensive and more sensitive determinations. •The identification and quantification of the furosine chromatographic signal was successfully achieved during analysis of commercial and spiked samples.